Biology, ecology, and uses of the medicinal plant Sesamum alatum - Edgar Cambaza (Academia Biology)
Introduction: Sesamum alatum is a herb, sometimes considered a weed, common in African and Asian countries. It is used as a food and medicine but receives little attention in the scientific literature. Therefore, studying it for more effective and sustainable use is essential.